BO‘LAJAK BOSHLANG‘ICH SINF O‘QITUVCHILARINI INTERDISIPLINAR YONDASHUV ASOSIDA O‘QUV FAOLIYATIGA JALB ETISH VA KREATIV FIKRLASHINI RIVOJLANTIRISH MEXANIZMLARI - Quchqorova, N.M.; Jumaniyazova, G.B. (SCIENCE and SOCIETY, 2025)
This article explores the pedagogical foundations of developing students’ creativity and metacognitive competencies based on an interdisciplinary approach. The article shows how interdisciplinary education encourages students to think more creatively, critically,independently, how to develop the ability to manage and analyze their own learning.